Using Item Response Theory to create a comprehensive vengefulness scale - Drew M. Parton; David Chester; Michael L. Crowe (Open Science Framework, 2022)
Individuals differ in their predispositions toward seeking revenge—their vengefulness. Although the psychological antecedents and contextual factors that promote revenge have been widely studied, the structure of vengefulness has received less focus. The first phase of this project attempted to expand and clarify the taxonomy of vengefulness by using a hierarchical exploratory factor analysis on a battery of some of the most common vengefulness measures. This second phase will use Item Response Theory to distill a new scale from the included items.
Keywords: Social Psychology; Quantitative Psychology; Social and Behavioral Sciences; Psychology; item response theory; personality; revenge; scale development; vengefulness